The Dominance Of EVA Over EPS, ROE, And Roce In Stock Return Analysis: The Nigerian Evidence. - Asuquo, Mary V.; Offiong, Patience E. (Advances in Social Sciences Research Journal, 2019)
The study examined the dominance of EVA over accounting measures of EPS, ROE and ROCE in the evaluation of stock returns in Banks in Nigeria. Data were obtained mainly from the Nigerian Stock Exchange (NSE) and the selected Money Deposits Banks in Nigeria. Data consisted of daily stock prices and the Banks’ Financial Reports for a period of ten years, 2008-2017. A total of ten (10) banks listed of NSE were selected making a total of one-hundred (100) observations. Both descriptive as well as analytical data techniques were adopted. The results of the findings, especially the relative information content analysis reveals that EVA does not dominate any of the three accounting measures of EPS, ROE and ROCE in stock returns evaluation. However, the incremental information content test result shows that complementing EVA with ROE gives a better assessment of stock returns than using these two measures independently. We, therefore, recommend that EVA should be adopted as a complementary measure to ROE in stock returns evaluation because it is a useful measure.